Draft genome sequence of newly isolated agarolytic bacteria Cellulophaga omnivescoria sp. nov. W5C carrying several gene loci for marine Polysaccharide degradation - Valdehuesa, Kris Niño G. (Animo Repository, 2018)
The continued research in the isolation of novel bacterial strains is inspired by the fact that native microorganisms possess certain desired phenotypes necessary for recombinant microorganisms in the biotech industry. Most studies have focused on the isolation and characterization of strains from marine ecosystems as they present a higher microbial diversity than other sources. In this study, a marine bacterium, W5C, was isolated from red seaweed collected from Yeosu, South Korea. The isolate can utilize several natural polysaccharides such as agar, alginate, carrageenan, and chitin. Genome sequence and comparative genomics analyses suggest that strain W5C belongs to a novel species of the Cellulophaga genus, from which the name Cellulophaga omnivescoria sp. nov. is proposed. Its genome harbors 3,083 coding sequences and 146 carbohydrate-active enzymes (CAZymes). Compared to other reported Cellulophaga species, the genome of W5C contained a higher proportion of CAZymes (4.7%). Polysaccharide utilization loci (PUL) for agar, alginate, and carrageenan were identified in the genome, along with other several putative PULs. These PULs are excellent sources for discovering novel hydrolytic enzymes and pathways with unique characteristics required for biorefinery applications, particularly in the utilization of marine renewable biomass. The type strain is JCM 32108T (= KCTC 13157BPT).